Pengaruh Moral, UU Harmonisasi Peraturan Perpajakan, dan Kondisi Keuangan Terhadap Kepatuhan Wajib Pajak UMKM - Syahrina, Nur Alvi; Hasanah, Nuramalia; Yusuf, Muhammad (LPPM Universitas Negeri Jakarta, 2024)
The purpose of this study is to analyze the effect of morals, tax harmonization laws, and financial status on the tax compliance of MSE taxpayers. This research is quantitative research and data analysis in the form of descriptive statistical analysis using IBM SPSS Statistics 25 software and multiple regression analysis on Microsoft Excel. In this study, distributed questionnaires containing questions are used as main data. to MSE owners in South Jakarta. To select a population sample, researchers used the 100 persons make up the sample size for this convenience sampling technique. The outcomes revealed that morale and harmonization of tax laws have a positive effect on MSE tax compliance, while financial status has a negative effect on MSE tax compliance. Future researchers are advised to conduct research with additional variables that might increase the impact on taxpayer tax compliance and with more supporting data in the form of both primary and secondary data.